Analisis penguasaan kompetensi pedagogik dan profesional mahasiswa calon guru matematika dalam mata kuliah micro-teaching - Linda Linda (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2017)
Penelitian ini bertujuan untuk mendeskripsikan penguasaan kompetensi pedagogik dan profesional mahasiswa calon guru matematika dalam mata kuliah micro-teaching di Universitas Sultan Ageng Tirtayasa Provinsi Banten. Penelitian ini merupakan penelitian deskriptif. Subjek sebanyak 16 mahasiswa yang dipilih secara acak dari 72 mahasiswa jurusan pendidikan matematika, Universitas Sultan Ageng Tirtayasa Provinsi Banten tahun ajaran 2014/2015. Objek penelitian adalah kompetensi pedagogik dan profesional mahasiswa calon guru matematika dalam mata kuliah micro-teaching di Universitas Sultan Ageng Tirtayasa Provinsi Banten. Data hasil penelitian dianalisis dengan melihat kriteria penguasaan kompetensi pedagogik dan profesional. Hasil penelitian menunjukkan bahwa penguasaan kompetensi pedagogik mahasiswa calon guru matematika dalam mata kuliah micro-teaching di Universitas Sultan Ageng Tirtayasa Provinsi Banten, berada pada kriteria baik. Penguasaan kompetensi profesional mahasiswa calon guru matematika Universitas Sultan Ageng Tirtayasa Provinsi Banten, berada pada kriteria kurang.Kata Kunci: kompetensi pedagogik, kompetensi profesional, micro-teaching An Analysis of Pedagogical and Professional Competence Mastery of Student Teachers of Mathematics in Micro-Teaching Course AbstractThe study aims to describe the mastery of the pedagogical competence and the professional competence of student teachers of mathematics in micro-teaching courses at the University of Sultan Ageng Tirtayasa in Banten Province. The study was descriptive research. The subjects were 16 students who were randomly selected from 72 students of the Department of Mathematics Education, University of Sultan Ageng Tirtayasa Banten, in the academic year of 2014/2015. The object of this research was the pedagogical competence and professional competence of student teachers. The data were analyzed by observing the criteria for pedagogical competence mastery and mastery of professional competence criteria. The results of study show that the pedagogical competence mastery of the student teachers in the subjects of micro-teaching at the University of Sultan Ageng Tirtayasa in Banten Province is in the good criterion. The mastery of the professional competence of the student teachers in the same subjects is not in a less criterion.Keywords: pedagogical competence, professional competence, micro-teaching